seed yield and quality in amaranthus as influenced by planting systems and harvest stages - Bindu L S (Department of Olericulture, College of Agriculture, 2007)
The present investigation on “Seed yield and quality in amaranthus as influenced by planting systems and harvest stages” was conducted at the Department of Olericulture and the Instructional Farm, College of Agriculture, Vellayani, Thiruvananthapuram during February - May, 2006. Five planting systems viz., transplanting 25 days, 20 days, 15 days after sowing, broadcasting and line sowing were tried with four harvest stages which were 30, 40, 50 and 60 days after flowering. Majority of the characters were significantly influenced by the direct as well as interaction effects of the planting systems and harvest stages. Among the planting systems the earliest flowering was shown by seedlings transplanted 20 days after sowing. Transplanting 25 days after sowing produced the tallest plants. Maximum seed yield per plot and per plant was found in plants transplanted 20 days after sowing. Seed quality characters like seed recovery percentage, germination percentage and vigour index was also highest in plants transplanted 20 days after sowing. Among harvest stages maximum seed yield per plot and per plant were shown by plants harvested 50 days after flowering while those harvested 30 days after flowering gave the highest seed recovery percentage. Seeds from plants harvested 40, 50 and 60 days after flowering showed high germination percentages with slight differences between the values.